New species and new synonymy in Neoibidionini (Coleoptera, Cerambycidae) - Santos-Silva, Antonio; Galileo, Maria Helena M. (Zootaxa, 2017)
Microibidion morrisi sp. nov. is described from Bolivia. Microibidion bimaculatum Mehl et al., 2015 is recorded from Bolivia. A key to species of Microibidion is provided. Compsibidion bicolor Martins et al., 2014 is synonymized with Calycibidion rubricolle Galileo & Martins, 2010.